DEKOMPOSISI WAVELET DATA SEISMIK BROADBAND DARI STASIUN WANAGAMA YOGYAKARTA PADA SAAT LETUSAN GUNUNG MERAPI 2010 - , DAIROH S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Eruption of Merapi volcano in 2010 has caused damages on seismic observation stations installed around the Merapi. In this thesis, noise separation of signal recorded at far distance, at Wanagama station, by wavelet decomposition has been done. The analysis was done by judging the value of frequency range of the volcanic event signal according to Minakami (1974) using software MATLAB R2006a. The result showed that the wavelet decomposition at order 5 (db5) on level 5 on detail 1 could decompose the seismic signal record and obtain the volcanic events signal characterization such as volcanic tremor, multiphase, low frequency, deep volcanotectonic (VTA), shallow volcano-tectonic (VT-B) and pyrocalstic flow events.